Плиоцен и плейстоцен Среднего Байкала - Мац В. Д. Виктор Давыдович; Покатилов А. Г. Анатолий Григорьевич; Попова С. М. Светлана Михайловна; Кравчинский А. Я.; Флоренсов Н. А. Николай Александрович (Новосибирск, Наука, 1982)
Авт. указаны на обороте тит. л.